Scenario-Based Case Study Method and the Functionality of the Section Called ‘from Production to Consumption’ from the Perspective of Primary School Students - TANERİ, Ahu (Asian Journal of Education and Training, 2018)
In this research, the aim was showing the evaluation of students on scenario-based case study method and showing the functionality of the studied section called ‘from production to consumption’. Qualitative research method and content analysis were used to reveal participants' experiences and reveal meaningful relations regarding problems of the research. The study consisted of 28 fourth grade students from the same classroom, in a public school of Central District of Ankara. The study group was selected by neutral assignment. Lesson plans and forms developed by the researcher were used to obtain qualitative data in the research, which was carried out as a doctoral thesis study. Four lesson plans have been developed in order to be able to achieve advances in the field of learning 'production, distribution and consumption' in the social studies course. Each lesson plan includes a case study associated with the achievement but not finalized, a finalized scenario script covering the case study, open-ended questions, and digital and printed resources. The evaluation form that has been prepared to assess the functionality of the used method, includes the open-ended questions prepared for evaluating the function of the unit in terms of the students and thus, forms the basic data collection tool of this research. According to qualitative results of students answers, using scenario-based case study method is a positive experience. Students are more active in the learning process, they are more caring and they pay more attention to the lessons. They want to use this method in other lessons in which they struggle to concentrate and by using this method they are more able to keep their focus.The results of this study show that scenario-based case study methods have been well received by the students, the learning process with this method is more functional and the learned information continues to be used in non-school settings.